2019
DOI: 10.3311/ppar.12722
|View full text |Cite
|
Sign up to set email alerts
|

Path Optimization in 3D Concrete Printing to Minimize Weak Bonds Formation

Abstract: 3D concrete printing has proven to be a highly favorable construction method in terms of time reduction, cost optimization, architectural flexibility, sustainability, energy use, and others. However, the quality of the final product certainly has a priority over all of these attractive features of the technology. Yet research has given little consideration to investigating the structural integrity of 3D printed concrete structures. Research states that printed structures exhibit sufficient strength as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Bos et al [17] mentioned that square nozzles should be tangent to the toolpath when moving the printhead to overcome the twisting of the filament. AlSakka et al [18] identified the optimal deposition path of the 3DCP, which reduces the weak bonds and preserves the buildability of the extruded material by using a discrete event model.…”
Section: Introductionmentioning
confidence: 99%
“…Bos et al [17] mentioned that square nozzles should be tangent to the toolpath when moving the printhead to overcome the twisting of the filament. AlSakka et al [18] identified the optimal deposition path of the 3DCP, which reduces the weak bonds and preserves the buildability of the extruded material by using a discrete event model.…”
Section: Introductionmentioning
confidence: 99%